Neocordulia maurocostai sp. nov. (Odonata, Anisoptera: Oxygastridae), a new species of Emerald dragonfly from western Pantepui region, Venezuela - Marmels, Jürg De (Zootaxa, 2024)
The new species is described and illustrated from two males (holotype: Venezuela, Amazonas State, Serranía del Cuao, Caño Negro, 1440 m elevation, 5.087°N, 67.438°W, deposited in the MIZA Odonata collection, Universidad Central de Venezuela, Faculty of Agronomy, Maracay). The new species differs from all other species so far known mainly in structure of posterior hamulus and cercus. The subgenus Mesocordulia May, 1992 is formally elevated to generic rank different from Neocordulia Selys, 1882.